Essentials of Healthcare Strategy and Performance Management A Practical Guide for Executives and Emerging Leaders. - Langabeer, James R., II, 1969-; Champagne-Langabeer, Tiffany (Oxford : Productivity Press, 2024)
Using pragmatic and real-world evidence, this book provides essential briefings on key topics that every current or aspiring leader needs to know in order to better manage strategy and achieve improved performance in their hospital or health system.
Creating an Optimistic and Story-Based Culture -- Entrepreneurial Thinking -- Intrapreneurs Unlock Innovation Internally -- Benefits of Being Entrepreneurial -- The Leadership Challenge -- Overcoming Challenges and Building a Culture of Innovation -- Chapter Summary -- Discussion Questions -- Key Terms -- References -- 8 Governance and Boards -- Governance Basics -- Governance Roles -- Building Better Boards -- Six Factors that Create Better Board Governance -- Empowerment and Leadership -- Board Effectiveness Reviews -- Chapter Summary -- Discussion Questions -- Key Terms -- References
Description based upon print version of record.
9 Growth Strategies
Keywords: Health services administration; BUSINESS & ECONOMICS / Leadership; MEDICAL / Health Care Delivery